A potential area of use for immune checkpoint inhibitors: Targeting bone marrow microenvironment in acute myeloid leukemia - Aru, Başak; Pehlivanoğlu, Cemil; Dal, Zeynep; Dereli-Çalışkan, Nida Nur; Gürlü, Ege; Yanıkkaya-Demirel, Gülderen (Frontiers in Immunology, 2023)
Acute myeloid leukemia (AML) arises from the cells of myeloid lineage and is the most frequent leukemia type in adulthood accounting for about 80% of all cases. The most common treatment strategy for the treatment of AML includes chemotherapy, in rare cases radiotherapy and stem cell and bone marrow transplantation are considered. Immune checkpoint proteins involve in the negative regulation of immune cells, leading to an escape from immune surveillance, in turn, causing failure of tumor cell elimination. Immune checkpoint inhibitors (ICIs) target the negative regulation of the immune cells and support the immune system in terms of anti-tumor immunity. Bone marrow microenvironment (BMM) bears various blood cell lineages and the interactions between these lineages and the noncellular components of BMM are considered important for AML development and progression. Administration of ICIs for the AML treatment may be a promising option by regulating BMM. In this review, we summarize the current treatment options in AML treatment and discuss the possible application of ICIs in AML treatment from the perspective of the regulation of BMM.